Serum investigation of antibodies against porcine circovirus 4 Rep and Cap protein in Jiangxi Province, China - Hu, Xifeng; Ding, Zhen; Li, Yu; Chen, Zheng; Wu, Huansheng (Frontiers in Microbiology, 2022)
In 2019, a novel porcine circovirus 4 (PCV4) was first identified in Hunan Province, China. The circular PCV4 DNA was detected in both diseased and healthy pigs. Recently, PCV4 prevalence surveys have been analyzed in many provinces in both China and South Korea with low positive rates. However, no serological data has been conducted to investigate the prevalence of PCV4 in pigs from Jiangxi Province. To address this issue, an indirect anti-PCV4 antibody enzyme-linked immunosorbent assay (ELISA) based on Cap and Rep protein as a coating antigen was established and applied to study the serum epidemiology of PCV4 in Jiangxi Province. Purified PCV4-His-tagged Cap and Rep were used as the coating antigen to develop an ELISA detection kit. There was no cross-reaction of the Cap/Rep-based ELISA with antisera against PCV2, TGEV and PRRSV, indicating a high specificity of this ELISA assay. The intra-assay coefficient variations (CVs) of Cap-based were 1.239%−9.796%, Rep-based 1.288%−5.011%, and inter-assay CVs of 1.167%−4.694% and 1.621%−8.979%, respectively, indicating a good repeatability. Finally, a total number of 507 serum samples were collected from Jiangxi Province to test for antibody prevalence of PCV4, and 17 (3.35%) and 36 (7.10%) of the samples were Cap and Rep antibody positive, respectively. In summary, our established ELISA kit could be used to detect PCV4 antibodies in serum with good repeatability and high specificity. In addition, field samples detection results showed that the antibody of PCV4 was poorly distributed in intensive pig farms in Jiangxi Province, China.